Removal of pathogenic bacterial biofilms by combinations of oxidizing compounds - Olmedo, Gabriela María (2015)
Bacterial biofilms are commonly formed on medical devices and food processing surfaces. The antimicrobials used have limited efficacy against the biofilms; therefore, new strategies to prevent and remove these structures are needed. Here, the effectiveness of brief oxidative treatments, based on the combination of sodium hypochlorite (NaClO) and hydrogen peroxide (H2O2) in the presence of copper sulfate (CuSO4), were evaluated against bacterial laboratory strains and clinical isolates, both in planktonic and biofilm states. Simultaneous application of oxidants synergistically inactivated planktonic cells and prevented biofilm formation of laboratory Escherichia coli, Salmonella enterica serovar Typhimurium, Klebsiella pneumoniae, and Staphylococcus aureus strains, as well as clinical isolates of Salmonella enterica subsp. enterica, Klebsiella oxytoca, and uropathogenic E. coli. In addition, preformed biofilms of E. coli C, Salmonella Typhimurium, K. pneumoniae, and Salmonella enterica exposed to treatments were removed by applying 12 mg/L NaClO, 0.1 mmol/L CuSO4, and 350 mmol/L H2O2 for 5 min. Klebsiella oxytoca and Staphylococcus aureus required a 5-fold increase in NaClO concentration, and the E. coli clinical isolate remained unremovable unless treatments were applied on biofilms formed within 24 h instead of 48 h. The application of treatments that last a few minutes using oxidizing compounds at low concentrations represents an interesting disinfection strategy against pathogens associated with medical and industrial settings.